Single-walled carbon nanotubes coated with ZnO by atomic layer deposition. (4th November 2016) - Pal, Partha P; Gilshteyn, Evgenia; Jiang, Hua; Timmermans, Marina; Kaskela, Antti; Tolochko, Oleg V; Kurochkin, Alexey V; Karppinen, Maarit; Nisula, Mikko; Kauppinen, Esko I; Nasibulin, Albert G
Abstract: The possibility of ZnO deposition on the surface of single-walled carbon nanotubes (SWCNTs) with the help of an atomic layer deposition (ALD) technique was successfully demonstrated. The utilization of pristine SWCNTs as a support resulted in a non-uniform deposition of ZnO in the form of nanoparticles. To achieve uniform ZnO coating, the SWCNTs first needed to be functionalized by treating the samples in a controlled ozone atmosphere. The uniformly ZnO coated SWCNTs were used to fabricate UV sensing devices. An UV irradiation of the ZnO coated samples turned them from hydrophobic to hydrophilic behaviour. Furthermore, thin films of the ZnO coated SWCNTs allowed us switch p-type field effect transistors made of pristine SWCNTs to have ambipolar characteristics.